IMPLEMENTASI SISTEM TUMPANGSARI RUMPUT UNGGUL DI KELOMPOK KUTASARI FARM PURBALINGGA UNTUK MENINGKATKAN KETERSEDIAAN PAKAN DOMBA - Danang Nur Cahyo; Prasetyo Prasetyo; Annistia Rahmadian Ulfah; Nur Hidayat; Titin Widiyastuti; Sri Rahayu; Indra Sugiharto (Universitas Mataram, 2025)
Kutasari Farm Group, located in Karangcegak Village, Kutasari District, Purbalingga Regency, primarily engages in sheep farming but has long struggled to provide a continuous supply of forage. This community service program aimed to enhance the knowledge, attitudes, and skills of the group members in forage crop cultivation. The program targeted 18 sheep farmers and adopted a Participatory Action Research (PAR) approach comprising the stages of problem identification, program design, implementation, monitoring, and evaluation. The implementation phase involved socialization, group discussions, and hands-on practice in forage planting, while the evaluation phase included pre-tests and post-tests to assess the training’s effectiveness. The results showed that 80% of participants were engaged in sheep farming, 46% had previously planted forage crops, and 66.7% were capable of practicing intercropping cultivation. After the training, farmers’ knowledge in forage cultivation increased to 93.3%, and 88% expressed willingness to continue participating in the program. Agronomic evaluation of the demonstration plots revealed that the plant heights of Gama Umami grass under the intercropping system, Pakchong grass, Red Napier grass, and Elephant grass (the group’s original forage) were 174 cm, 172 cm, 173 cm, and 101 cm, respectively. These findings indicate a substantial improvement in farmers’ knowledge of forage cultivation, with the intercropping system achieving a 72.2% higher plant height compared to the previously cultivated forage. The results of the training also showed an increase in knowledge and group dynamics of Kutasari Farm.